Rigor/Us: Building Boundaries and Disciplining Diversity with Standards of Merit. Issue 3 (2nd September 2017) - Riley, Donna
ABSTRACT: Rigor is the aspirational quality academics apply to disciplinary standards of quality. Rigor's particular role in engineering created conditions for its transfer and adaptation in the recently emergent discipline of engineering education research. 'Rigorous engineering education research' and the related 'evidence-based' research and practice movement in STEM education have resulted in a proliferation of boundary drawing exercises that mimic those in engineering disciplines, shaping the development of new knowledge and 'improved' practice in engineering education. Rigor accomplishes dirty deeds, however, serving three primary ends across engineering, engineering education, and engineering education research: disciplining, demarcating boundaries, and demonstrating white male heterosexual privilege. Understanding how rigor reproduces inequality, we cannot reinvent it but rather must relinquish it, looking to alternative conceptualizations for evaluating knowledge, welcoming diverse ways of knowing, doing, and being, and moving from compliance to engagement, from rigor to vigor.